Influence Of Social Media Marketing Instagram on Interest in Buying Books at Gramedia.Com - Nahda Ratu Aulia; Cecep Safa’atul Barkah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to determine the effect of social media marketing on book buying interest in Gramedia.com, given the increasing number of active social media users in Indonesia and the role of social media, especially Instagram, in company marketing activities. The object of this research consists of independent variables, namely social media marketing and the dependent variable of buying interest. The method used is quantitative with a descriptive verification approach and survey as a data collection tool. Analysis was carried out through simple linear regression, normality test, heteroscedasticity test, coefficient of determination, and hypothesis testing. The research population is Instagram followers @gramedia.com, with sampling using purposive sampling technique totaling 100 respondents. The results showed a positive influence between social media marketing and purchase intention, where the better the application of social media marketing, the higher the level of purchase intention. Based on hypothesis testing, it can be concluded that social media marketing significantly has a positive effect on buying interest in books at Gramedia.com.